An Automated Dna Strands Detection System Featuring 32-Bit Arm7tdmi Microcontroller And Vga-Cmos Digital Image Sensor. - Mohd Noor, Mohd Halim (2009)
Genetic DNA recognition is a routine experiment for detecting the origin of the species. Electrophoresis is one of the processes for such detection which has been used extensively.